(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article defines the essence of sports tourism, gives the basis of the difference between sports tourism and sports and health tourism. The main directions of modern sports tourism - route tourism and competitions are described. The article highlights the features of the development of sports tourism on the example of one of the Carpathian regions - Ivano-Frankivsk region. The impact of the period of quarantine restrictions on the tourism sector of the region and the period of recovery of tourist flows in 2021 is estimated. Measures to develop the tourist infrastructure of Ivano-Frankivsk region are analyzed. Measures to promote the tourist potential of Ivano-Frankivsk region were evaluated. The list of tourist objects created at the expense of the state financing and private investments is defined. The main problems that remain and need to be addressed to promote tourism in the Carpathian region are identified. The list of measures of the Regional target program of tourism development in Ivano-Frankivsk region for 2022-2026 is presented. The article offers the purposes and tasks for development of sports tourism in Ivano-Frankivsk region. A cognitive-sports tourist route has been developed to popularize sports tourism in the Carpathian region. The cognitive-sports tourist route will include the following tourist objects: Manyavsky temple, Manyavsky waterfall, Carpathian volcano. Sports and educational tourist route «Manyavsky waterfall» is created on the principle of accessibility for all stakeholders. Maintenance and use of the route will be provided to local communities.